2018
DOI: 10.1186/s12974-018-1248-8
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease patients have a complex phenotypic and functional Th1 bias: cross-sectional studies of CD4+ Th1/Th2/T17 and Treg in drug-naïve and drug-treated patients

Abstract: BackgroundParkinson’s disease (PD) affects an estimated 7 to 10 million people worldwide, and only symptomatic treatments are presently available to relieve the consequences of brain dopaminergic neurons loss. Neuronal degeneration in PD is the consequence of neuroinflammation in turn influenced by peripheral adaptive immunity, with CD4+ T lymphocytes playing a key role. CD4+ T cells may however acquire proinflammatory phenotypes, such as T helper (Th) 1 and Th17, as well as anti-inflammatory phenotypes, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
224
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(247 citation statements)
references
References 61 publications
16
224
0
7
Order By: Relevance
“…For example, a recent study showed that PD patients had lower levels of helper T cells (Th) 2, Th17, and regulatory T cells in the blood, compared to age-and sex-matched healthy controls. 47 It is therefore tempting to speculate that the lower risk of PD in relation to higher concentration of lymphocytes as shown in our study might be due to the increased levels of these specific T-cell subsets. Furthermore, because the concentrations of leukocytes and haptoglobin observed in our study are within the normal ranges, these measurements are unlikely directly useful as predictive biomarkers in the diagnosis of PD.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, a recent study showed that PD patients had lower levels of helper T cells (Th) 2, Th17, and regulatory T cells in the blood, compared to age-and sex-matched healthy controls. 47 It is therefore tempting to speculate that the lower risk of PD in relation to higher concentration of lymphocytes as shown in our study might be due to the increased levels of these specific T-cell subsets. Furthermore, because the concentrations of leukocytes and haptoglobin observed in our study are within the normal ranges, these measurements are unlikely directly useful as predictive biomarkers in the diagnosis of PD.…”
Section: Discussionmentioning
confidence: 66%
“…Although we agree that peripheral adaptive immunity is involved in PD, we have relatively little knowledge about the detailed peripheral immune phenotypes in PD. For example, a recent study showed that PD patients had lower levels of helper T cells (Th) 2, Th17, and regulatory T cells in the blood, compared to age‐ and sex‐matched healthy controls . It is therefore tempting to speculate that the lower risk of PD in relation to higher concentration of lymphocytes as shown in our study might be due to the increased levels of these specific T‐cell subsets.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, examination of the CD4‐Th subpopulations suggests an abnormal distribution with the effector memory (antigen‐experienced) fraction overrepresented in detriment to the naïve T‐cells (Bas et al., ; Fiszer et al., ; Saunders et al., ; Stevens et al., ). A recent study reported that the reduction in CD4‐Th cells in PD patients is due to a decrease in Th2, Th17, and regulatory T‐cell populations; furthermore the authors reported that CD4‐Th cells from PD patients show a Th1‐biased immune response with increased IFN‐gamma and TNF production, strongly suggesting involvement of CD4 cells in the pathophysiology of the disease (Kustrimovic et al., ).…”
Section: The Adaptive Immune System Is Also Involved In Parkinson's Dmentioning
confidence: 99%
“…Supporting a possible role of IFN-γ in the disease process, increased levels of IFN-γ in the serum, as well as increased production of IFN-γ by peripheral CD4+ T cells, have been detected in PD patients compared to healthy controls 11,12 . Moreover, a significant co-expression of α -synuclein and IFN-γ has been found within the substantia nigra of PD patients 13 .…”
Section: Introductionmentioning
confidence: 85%
“…Increased IFN-γ levels have been documented in PD patients 11,12 . The source of IFN-γ in the aged and PD brain still needs to be identified.…”
Section: Discussionmentioning
confidence: 99%